Novel Microstrip Ultra-Wideband Bandpass Filter Using Radial-Stub-Loaded Structure - Xida Deng; Kai Da Xu; Zhigang Wang; Bo Yan (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A novel planar ultra-wideband (UWB) bandpass filter (BPF) using radial-stub-loaded resonator is proposed, where the resonator consists of three radial stubs, one located in the middle and two symmetrically at both sides. This radial-stub-loaded structure situates the first four resonant modes in the UWB passband (3.1 10.6 GHz) and makes the fifth resonant mode far away from this passband. To enhance the coupling degree, two interdigital coupled feed lines are utilized in this UWB filter. Finally, a UWB BPF with wide upper-stopband and sharp upper rejection skirt has been realized and its design steps have been also presented. The measured and full-wave simulated results of the proposed filter are in good agreement.